2006
DOI: 10.1113/jphysiol.2005.098723
|View full text |Cite
|
Sign up to set email alerts
|

Transvascular fluid flux from the pulmonary vasculature at rest and during exercise in horses

Abstract: Exercise causes changes in pulmonary haemodynamics through redistribution of blood flow, increase in the pulmonary surface area, and increase in pulmonary vascular pressures. These changes contribute to the increase in fluid exchange across the alveolar-capillary barrier. To determine the extent of the fluid exchange across the alveolar-capillary barrier at rest and during exercise, six horses were exercised on a high-speed treadmill until fatigue. Arterial and mixed venous blood were sampled at rest and durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(54 citation statements)
references
References 43 publications
2
52
0
Order By: Relevance
“…Vengust et al . (2006) reported that horses undergoing intense exercise experience a loss of fluid from the pulmonary capillaries into the lung interstitium, which is probably due to increased pulmonary microvascular pressures and a decreased colloid osmotic gradient in response to fluid release from erythrocytes secondary to high O 2 tension in the lungs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vengust et al . (2006) reported that horses undergoing intense exercise experience a loss of fluid from the pulmonary capillaries into the lung interstitium, which is probably due to increased pulmonary microvascular pressures and a decreased colloid osmotic gradient in response to fluid release from erythrocytes secondary to high O 2 tension in the lungs.…”
Section: Discussionmentioning
confidence: 99%
“…This occurrence seems unlikely in our study as the lost fluid would have to be hypertonic with respect to sodium and protein in order to explain our results. However, it is possible that during the course of exercise, movement of water or other nonprotein containing fluid from erythrocytes (Vengust et al . 2006) and/or surrounding tissues into the pulmonary microvasculature contributed to the small, but significant, observed differences between pl[Na + ] a and pl[Na + ] v and [TP] a and [TP] v .…”
Section: Discussionmentioning
confidence: 99%
“…Within 2 min of the onset of heavy exercise in horses, approximately 12 l/min or 4% of cardiac output moves from the pulmonary circulation into the pulmonary interstitium (Vengust et al . 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…2001). During our previous study we have shown that erythrocytes are major contributors to pulmonary transvascular fluid fluxes (Vengust et al . 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…1997; Juel et al . 1999), which is evident as the erythrocyte regulatory volume decrease in peripheral tissues, and by the erythrocyte regulatory volume increase across the lung (Vengust et al . 2006a,b).…”
Section: Discussionmentioning
confidence: 99%